Development of a QR Code-Based Interactive Textbook for Basic Embroidery Techniques - Armaini Rambe; Eka Rahma Dewi; Yudhistira Anggraini; Juliarti Juliarti (Sakura Digital Nusantara, 2026)
Purpose: This study aimed to develop and evaluate the feasibility of a QR Code-based interactive textbook for thread embroidery to support learning in the Basic Embroidery Techniques course of the Fashion Design Education Study Program at Universitas Negeri Medan. Methods: This research employed a Research and Development (R&D) approach using the Four-D (4D) model, consisting of the Define, Design, Develop, and Disseminate stages. The product was validated by two material experts and two media experts before being tested with students through three stages: a small-group trial (3 students), a medium-group trial (7 students), and a large-group trial (30 students). Student participants were selected using simple random sampling. Data were collected using expert validation sheets and user response questionnaires and analyzed descriptively using percentage-based feasibility criteria. Findings: The material expert validation yielded a feasibility score of 84.70%, while the media expert validation reached 83.57%, both classified as very feasible. Product trials also demonstrated high feasibility, with scores of 82% in the small-group trial, 88% in the medium-group trial, and 95% in the large-group trial. The overall findings indicate that the developed textbook met the established feasibility criteria and received positive acceptance from users. Research Implications: The developed textbook provides an alternative technology-integrated teaching resource for vocational education by combining printed instructional materials with QR Code-linked digital content. The product is considered feasible for use as a learning resource in basic embroidery instruction. Originality: The novelty of this study lies in the development of a QR Code-based interactive textbook that integrates conceptual explanations, visual illustrations, and digital learning resources into a single instructional medium specifically designed for thread embroidery learning in Fashion Design Education.